Effectiveness of mindfulness-based stress reduction program on quality of life in cardiovascular disease patients - Jalali, Darioush (Int J Cardiol Heart Vasc, 2019)
INTRODUCTION: Cardiovascular disease is one of the most fatal physical illnesses that impose many financial losses on societies every year. AIM: This study was to investigate the effectiveness of a mindfulness-based stress reduction (MBSR) program on self-efficacy and quality of life in patients with cardiovascular disease. MATERIAL AND METHODS: The samples of this clinical trial were 60 patients who were selected by convenience sampling from patients were diagnosed, clinically interviewed by a cardiologist and randomized to two groups; experimental and control, and then completed Sherer et al. General Self-Efficacy Scale and 36-item Short Form Survey three times; pre-test, post-test, and after 3 months of follow-up. MBSR Program includes the methods that patients learn to calm their minds and body to help them cope with disease that was based on self-efficacy and quality of life. Data analysis was performed by the SPSS v22 using t-test and ANOVA. RESULTS: The results show that the mean pre-test scores of self-efficacy and quality of life of patients were not significantly different between the experimental and control groups (P > 0.05). However, the mean scores of the two variables were found to be significantly different between the experimental group and the control group on the post-test and follow-up as the research hypotheses were examined (P < 0.01). So that the means of self-efficacy were 60.80 ± 5.91 and 60.40 ± 7.03 and quality of life were 103.80 ± 9.35 and 101.10 ± 9.13 at post-test and 3 months later respectively in experimental group. CONCLUSION: Self-efficacy and quality of life of cardiovascular patients could be improved by providing an MBSR program.